Radiocesium in lichens and reindeer after the Chernobyl accident - Rissanen, K.; Rahola, T. (Rangifer, 1990)
After the Chernobyl accident the sampling and measuring program of the Finnish Centre for Radiation and Nuclear Safety was intensified both for surveillance and research purposes. The deposition pattern of radionuclides was more complicated than from the global fallout after the nuclear weapons tests. The radioactive deposition was very unevenly distributed in Lapland, as also in the rest of Finland. Fortunately, the amounts of deposition in Lapland were only about one-tenth of the corresponding amount of deposition in southern Finland. In 1986-87 the mean concentration of Cs-137 in lichens and in reindeer meat increased to about the same level as in 1972-73 or to about 30 per cent of the maximum levels found in 1964-65 after the nuclear weapons tests. The activity concentrations in reindeer tissues vary according to season. In winter, reindeer eat considerable amounts of lichens with high radiocesium concentrations. In summer, lichens are replaced by other forage such as leaves from trees, green plants, etc. The ratio of Cs-137 concentration in reindeer meat between summer and winter is about 0.2. The mean concentration of Cs-137 in meat for consumption from the slaughtering period 1986-87 was 720 Bq/kg fresh weight. After that time concentrations started decreasing since no new fallout was deposited.